2021
DOI: 10.1002/pol.20210330
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of ionic liquid and polymer and its implications for polymerized ionic liquids: An overview towards a new theory and simulation

Abstract: Ionic liquid (IL)‐containing polymers garner attention for electrochemical applications. This article overviews recent experimental and theoretical studies of polymer electrolytes that would be likely to cultivate new theoretical and computational frameworks for IL‐containing polymers. The first two sections outline the uniqueness of ILs that differentiates them from inorganic salts in polymers and explore deviation from the concept of the metaphor “room‐temperature molten salt.” Such distinct properties inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 231 publications
0
12
0
Order By: Relevance
“…The improvement in ionic conductivity can be attributed to the screening of interfacial interactions of nanocellulose framework by absorbed PILs that facilitate ion liquid transport through open continuous pores with minimum dissipation of energy. 45,46 3.4. Energy Storage Performance Demonstration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The improvement in ionic conductivity can be attributed to the screening of interfacial interactions of nanocellulose framework by absorbed PILs that facilitate ion liquid transport through open continuous pores with minimum dissipation of energy. 45,46 3.4. Energy Storage Performance Demonstration.…”
Section: Resultsmentioning
confidence: 99%
“…The known electrolyte materials are categorized based on their solvent by aqueous, organic, and ionic liquid-based and emphasis was given to supercapacitors that used carbonbased electrodes (rGO and other carbon materials) for comparison reasons and to avoid any pseudocapacitive contributions. 13,45,54,55 Comparison was conducted to other ionic liquid-based electrolytes reported to date, such as poly(vinyl alcohol) (PVA)/cross-linked poly(2-hydroxyethyl methacrylate) (C-pHEMA)/60 wt % EMIMBF 4, 50 poly-(vinylidene fluoride) (PVDF)/ZIF-8/74 wt % EMITFSI, 56 polyoxyethylene/nitrile butadiene rubber (PEO/NBR) with 70 wt % EMIBF 4, 59 epoxy/Al 2 O 3 /50 wt % BMIM-TFSI/ LiTFSI, 13 and PVA/35 wt % BMIMCl-Li 2 SO 4 (Figure 7b). 50 The CNF-based ionogels demonstrated comparable specific energy values (36.9−37.5 Wh/kg) resulting from the high ionic liquid content (88−90 wt %) and the porous CNF networks that accommodate ion-transport (Figure 7b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown that in both ionic liquid and polymer electrolytes, the ionic interactions between Li + and other ions or ionic functional groups can have an important impact on ion transport, aggregation and even the formation of conducting nanochannels. 39,49 In the zwitterion electrolytes, the tethered cationic and anionic species could change the polarizability, aggregation and ion transport characteristics compared to the OIPC systems. Future work, including simulation studies, will be used to further understand these differences.…”
Section: Ionic Conductivitymentioning
confidence: 99%